3D printed zirconia dental implants with integrated directional surface pores combine mechanical strength with favorable osteoblast response. (15th September 2022) - Zhang, Fei; Spies, Benedikt C.; Willems, Evita; Inokoshi, Masanao; Wesemann, Christian; Cokic, Stevan M.; Hache, Benedikt; Kohal, Ralf J.; Altmann, Brigitte; Vleugels, Jef; Van Meerbeek, Bart; Rabel, Kerstin
Abstract: Dental implants need to combine mechanical strength with promoted osseointegration. Currently used subtractive manufacturing techniques require a multi-step process to obtain a rough surface topography that stimulates osseointegration. Advantageously, additive manufacturing (AM) enables direct implant shaping with unique geometries and surface topographies. In this study, zirconia implants with integrated lamellar surface topography were additively manufactured by nano-particle ink-jetting. The ISO-14801 fracture load of as-sintered implants (516±39 N) resisted fatigue in 5–55 °C water thermo-cycling (631±134 N). Remarkably, simultaneous mechanical fatigue and hydrothermal aging at 90 °C significantly increased the implant strength to 909±280 N due to compressive stress generated at the seamless transition of the 30–40 µm thick, rough and porous surface layer to the dense implant core. This unique surface structure induced an elongated osteoblast morphology with uniform cell orientation and allowed for osteoblast proliferation, long-term attachment and matrix mineralization. In conclusion, the developed AM zirconia implants not only provided high long-term mechanical resistance thanks to the dense core along with compressive stress induced at the transition zone, but also generated a favorable osteoblast response owing to the integrated directional surface pores. Statement of significance: Zirconia ceramics are becoming the material of choice for metal-free dental implants, however significant efforts are required to obtain a rough/porous surface for enhanced osseointegration, along with the risk of surface delamination and/or microstructure variation. In this study, we addressed the challenge by additively manufacturing implants that seamlessly combine dense core with a porous surface layer. For the first time, a unique surface with a directional lamellar pore morphology was additively obtained. This AM implant also provided strength as strong as conventionally manufactured zirconia implants before and after long-term fatigue. Favorable osteoblast response was proved by in-vitro cell investigation. This work demonstrated the opportunity to AM fabricate novel ceramic implants that can simultaneously meet the mechanical and biological functionality requirements. Graphical abstract: Image, graphical abstract